2009
DOI: 10.1111/j.1365-2672.2009.04373.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation and elimination of human enteric viruses by Pacific oysters

Abstract: Aims:  To investigate the comparative elimination of three different human enterically transmitted viruses [i.e. hepatitis A virus (HAV), norovirus (NoV) and poliovirus (PV)] and inactivation of HAV and PV by Pacific oysters. Methods and Results:  New Zealand grown Pacific oysters (Crassostrea gigas) were allowed to bioaccumulate HAV, NoV and PV. Samples of oyster gut, faeces and pseudofaeces were then analysed by using real‐time RT‐PCR to determine the amount of viral RNA and cell culture methods to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 48 publications
2
38
0
Order By: Relevance
“…The application of quantitative virus detection methods for MST of contaminated shellfish may complicate the picture further, as virus uptake, bioaccumulation, and persistence in shellfish were previously shown to be virus specific and to vary between seasons and shellfish species (2,28,33). The specific binding of NoV to certain carbohydrates in the digestive tract of oysters, mussels, and clams was demonstrated recently (28,46).…”
Section: Discussionmentioning
confidence: 99%
“…The application of quantitative virus detection methods for MST of contaminated shellfish may complicate the picture further, as virus uptake, bioaccumulation, and persistence in shellfish were previously shown to be virus specific and to vary between seasons and shellfish species (2,28,33). The specific binding of NoV to certain carbohydrates in the digestive tract of oysters, mussels, and clams was demonstrated recently (28,46).…”
Section: Discussionmentioning
confidence: 99%
“…Enteric viruses have previously been shown to be distributed throughout oyster tissues, such as in the gills and the digestive tract (33,54,55). To determine the proportion of viruses distributed within hemocytes compared to tissues, hemolymph was removed from whole oysters by direct draw with a pipette after shucking.…”
Section: Isolation Of Viruses From Hemocytesmentioning
confidence: 99%
“…A review of the research literature suggests that viruses differ in the ability to persist within shellfish (6,29,39,48,53). For example, McLeod et al (33) recently showed that HAV and HuNoV levels in oysters did not decrease significantly after a 23-h depuration period, while poliovirus (PV) levels declined substantially. Kingsley and Richards (29) demonstrated that HAV could be detected in oysters for as long as 6 weeks after exposure to virus-contaminated water, while Ueki et al (53) showed that feline calicivirus (FCV), a HuNoV surrogate, does not persist in oysters.…”
mentioning
confidence: 99%
“…Provost et al (2011) (hematocytes) (acidic digestion) . feline calicivirus murine norovirus (Mcleod et al, 2009b;Nappier et al, 2008;Provost et al, 2011;Ueki et al, 2007).…”
Section: Real Time Rt-pcrmentioning
confidence: 99%
“…(Le Guyader et al, 2006;Mcleod et al, 2009aMcleod et al, , 2009bTian et al, 2006;Wang et al, 2008), (Maalouf et al, 2010;Nappier et al, 2008). Provost et al (2011) (hematocytes) (acidic digestion) .…”
Section: Real Time Rt-pcrmentioning
confidence: 99%